Hubungan adversity quotient dengan intensi berwirausaha pada siswa jurusan kuliner SMK Padang - Widya Utami Nasution; Yantri Maputra; Rozi Sastra Purna (University of Merdeka Malang, 2021)
This study aimed at testing the correlation between adversity quotient and entrepreneurship intention on culinary art students of SMKN 9 Padang. The proposed hypothesis is there is a correlation between adversity quotient and entrepreneurship intention on culinary art students of SMKN 9 Padang. Sampling technique used in this research is purposive sampling technique with 149 students as research sample. The instrument used are adversity quotient scale that is consist of 44 items (rx-0,884) and entrepreneurship intention scale that is consist of 20 items (rx=0,980). The data was analyzed with product moment from Pearson analysis. Using SPSS program resulted in the value of r=594 with p=0,000 (p0,001). The result of the study indicated that adversity quotient correlated positively with the entrepreneurship intention on the culinary students of SMKN 9 Padang.